How preferences shape the welfare and employment effects of trade - Hartmut Egger; Simone Habermeyer (Review of World Economics, 2021)
We set up a trade model with two countries, two sectors, and one production factor, which features a home-market effect due to the existence of trade costs. We consider search frictions and firm-level wage bargaining in the sector producing differentiated goods and a perfectly competitive labor market in the sector producing a homogeneous good. Consumers have price-independent generalized-linear preferences over the two types of goods, covering homothetic and quasi-homothetic preferences as two limiting cases. Due to the specific functional forms of indirect utility, homothetic preferences lead to risk aversion, while quasi-homothetic preferences lead to risk neutrality in our model. We show that trade between two countries that differ in their population size leads to an expansion of the differentiated goods sector and a contraction of the homogeneous good sector in the larger economy. This induces the larger country to net-export differentiated goods at the cost of a higher economy-wide rate of unemployment in the open economy (with the effects reversed for the smaller country). The welfare effects of trade depend on the preference structure. Looking at the two limiting cases, we show that the larger country is likely to benefit from trade if preferences are homothetic, whereas losses from trade are possible if preferences are quasi-homothetic. The opposite is true in the smaller country. This reveals an important role of preferences for the welfare effects of trade in the presence of labor market imperfection, a result we further elaborate on by considering more general preferences as well as differences of countries in their per-capita income levels.
Keywords: F12; F15; F16; D11; 330; Preferences; Search frictions; Wage bargaining; Trade structure; Welfare and employment effects